Ozanimod (RPC1063) is a potent sphingosine‐1‐phosphate receptor‐1 (S1P(1)) and receptor‐5 (S1P(5)) agonist with autoimmune disease‐modifying activity - Scott, F L (Br J Pharmacol, 2016)
BACKGROUND AND PURPOSE: Sphingosine1‐phosphate (S1P) receptors mediate multiple events including lymphocyte trafficking, cardiac function, and endothelial barrier integrity. Stimulation of S1P(1) receptors sequesters lymphocyte subsets in peripheral lymphoid organs, preventing their trafficking to inflamed tissue sites, modulating immunity. Targeting S1P receptors for treating autoimmune disease has been established in clinical studies with the non‐selective S1P modulator, FTY720 (fingolimod, Gilenya™). The purpose of this study was to assess RPC1063 for its therapeutic utility in autoimmune diseases. EXPERIMENTAL APPROACH: The specificity and potency of RPC1063 (ozanimod) was evaluated for all five S1P receptors, and its effect on cell surface S1P(1) receptor expression, was characterized in vitro. The oral pharmacokinetic (PK) parameters and pharmacodynamic effects were established in rodents, and its activity in three models of autoimmune disease (experimental autoimmune encephalitis, 2,4,6‐trinitrobenzenesulfonic acid colitis and CD4(+)CD45RB(hi) T cell adoptive transfer colitis) was assessed. KEY RESULTS: RPC1063 was specific for S1P(1) and S1P(5) receptors, induced S1P(1) receptor internalization and induced a reversible reduction in circulating B and CCR7(+) T lymphocytes in vivo. RPC1063 showed high oral bioavailability and volume of distribution, and a circulatory half‐life that supports once daily dosing. Oral RPC1063 reduced inflammation and disease parameters in all three autoimmune disease models. CONCLUSIONS AND IMPLICATIONS: S1P receptor selectivity, favourable PK properties and efficacy in three distinct disease models supports the clinical development of RPC1063 for the treatment of relapsing multiple sclerosis and inflammatory bowel disease, differentiates RPC1063 from other S1P receptor agonists, and could result in improved safety outcomes in the clinic.